Operational efficiency and productivity in container terminals (I) : PSA background and competitiveness - Goh, Wen Cai. (2010)
The purpose of this report is to study the strengths of PSA Singapore container terminals and the potential for further efficiency improvements, as well as to investigate the feasibility of improving the different aspects of operations in order to improve customer satisfaction. There is an increasing amount of container volume flowing through the world and this has brought about a wave of consolidation in the container liner companies through a series of merger and acquisitions. As such the shipper-port relations have changed and container lines now have greater power to influence a major port‘s container volume. It is thus important for ports to improve to face the increase in demand from the container lines. For the port of Singapore, being the top transhipment port in the world, the increase world‘s container volume means that Singapore must increase its handling capacity without significantly increasing its cost. Physical means of increasing capacity (i.e. expansion of port area) is not possible for Singapore due to land scarcity. Thus Singapore has the choice of improving its operational efficiencies or customer service. Singapore already has very high productivity through integration of IT into operations. Customers also express high satisfaction with the infrastructure of Singapore container terminals. As such, it is important for Singapore to look into improving customer service.